An interdisciplinary approach to address aquatic environmental issues with young students from Brazil. Issue 1 (2nd January 2022) - Scoarize, Matheus Maximilian Ratz; Contieri, Beatriz Bosquê; Delanira-Santos, Driele; Zanco, Bárbara Furrigo; Benedito, Evanilde
Abstract: Environmental education aims to change the perception of people about the environment. Primary education (four to eleven years old) is a fundamental stage in the development of children's conduct, so enhancing learning of the environment in which they live is essential for them to start recognizing nature as part of their life. We tested students' perception before (pre-test) and after (post-test) a specific environmental education activity elaborated in a ludic and interdisciplinary way (psychological, biological, performing arts and educational perspectives), with more moments of practice than only theoretical or rhetorical. Our study showed that schools located in cities with low Municipal Human Development Index (MHDI) can present satisfactory results in relation to students' environmental perception (hypothesis 1), that this perception does not differ according to nationwide educational indexes such as the Brazilian Basic Education Development Index (IDEB) (2), and that regardless of MHDI, there is an increase in this perception after environmental education activities, even a single activity (3). The developed methodology was effective in changing students' environmental perception, and can be used in an interdisciplinary way, even when resources are scarce.